Islamic Law Shapes Sociological Life (Sociology of Islamic Law) - Maysarah; Maria Ulfa (International Journal of Global Sustainable Research, 2023)
This research aims to determine the role of Islamic legal sociology in shaping the reciprocal sociological life of changes in law and society. Changes in law can influence changes in society and conversely changes in society can influence changes in law, including Islamic law. In general, the scope of legal sociology is to explain the influence of certain societal cultural patterns and social behavior on legal thinking and change. However, it can be determined that the location or scope of legal sociology is divided into 2, namely, a. Viewed from the social foundations of law. The benefits of legal sociology for understanding the operation of law in society can be seen from the function of law in society. The function of law in question can be observed from various points of view, such as the function of law as social control in society, the function of law as a tool for changing society, the function of law as a symbol of knowledge, the function of law as a political instrument, and the function of law as a tool of integrity.